Sexist advertising in Costa Rica: a longitudinal study in radio and television - Ordoñez Lacle, Camila (2025)
Introduction and Objective: This study examined the evolution of sexism in radio and television advertising discourse within the Costa Rican context, conceptualizing advertising as a mechanism of informal education and gender socialization, and assessing the detrimental impact of sexist advertising narratives on gender equality and women's rights enjoyment. Methodology: A quantitative and longitudinal study was conducted. The 40 most frequently aired radio and television advertisements were extracted in equal proportions from equivalent periods in 2015 and 2021, and five experts evaluated their sexism levels using a Likert scale. The final sample comprised 200 expert judgment assessments. Results: Statistical analysis reveals the persistence over time of undesirable levels of sexism in advertising, although with a significant decrease in stereotypes regarding women's roles in the household and family. Additionally, a higher level of sexism was registered in television advertising. Conclusions: The findings indicate that it is necessary to expand research along these lines and strengthen actions for advertising co-regulation with a gender and intersectional perspective.